Repositioning Waqf as an Islamic Legal and Social Institution: A Global Bibliometric and Thematic Review (1975–2025) - Moh. Asep Zakariya Ansori; Oyo Sunaryo Mukhlas; Fauzan Ali Rasyid; Mohamad Sar’an (Journal of Legal and Cultural Analytics, 2026)
This study repositions waqf as an Islamic legal and social institution by mapping the evolution, intellectual structure, and thematic development of global waqf scholarship from 1975 to 2025. Using a mixed-method review, it integrates bibliometric analysis and thematic content analysis of 319 Scopus-indexed journal articles, supported by Google Scholar triangulation. The results show a major acceleration of publications after 2010, alongside a shift from doctrinal-historical studies toward governance- and finance-oriented research. Four dominant thematic clusters emerge: cash waqf, governance and accountability, Islamic social finance integration, and institutional management. However, the literature remains geographically concentrated, collaboration networks are fragmented, and empirical impact evaluation is still limited. The study highlights critical gaps for strengthening Islamic legal theory, socio-legal analysis, and evidence-based waqf governance reform.